Metabolic syndrome in psychiatric outpatients in a tertiary care center in Eastern India - Chakraborty, Kaustav; Chatterjee, Moumita; Bhattacharyya, Ranjan; Dan, Amitava; Neogi, Rajarshi (International Journal Of Community Medicine And Public Health, 2020)
Background: Metabolic syndrome (MS) refers to a clustering of metabolic risk factors and compared to the general population, the prevalence of MS and its components is higher in populations with mental illness across all major diagnostic groups. Aim was to study the prevalence and correlates of MS in a cohort of psychiatric outpatients in a tertiary care centre in Eastern India. Methods: One hundred and sixty-four consecutive patients attending the outpatient service of Department of Psychiatry were recruited. The sociodemographic, clinical and physical activity profile of these patients were recorded by using a proforma specially designed for this purpose. Metabolic syndrome (MS) was diagnosed by the International Diabetic Federation criteria (IDF, 2006). Results: A typical subject was: married (64.6%), male (63.4%) and aged 38.76 years. The most common ICD-10 diagnostic categories were unipolar depression (28%), neurotic, stress related and somatoform disorders (28%), psychoses (21.9%), and bipolar disorder (9.7%). The mean age for onset and duration of illness were 31.65 years and 79 months respectively. The mean number and duration of psychotropic medication received by the subjects were 2.51 and 25.9 months respectively. An IDF criteria-based diagnosis of MS was made in 39% cases. A diagnosis of MS had a significant positive correlation with age, age at onset, duration since onset, number of comorbid medical illness, duration and number of psychotropic medications received, depressive disorders, and BMI. Conclusions: MS is common among subjects with psychiatric disorders and the prevalence of MS in our sample was consistent with the findings reported in literature.